The optimum marketing time for broilers, agricultural year 1966 - Barroso, Nilo Alberto; Albuquerque, J. Jackson L. de; Silva, Alaete Vieira da (Pesquisa Agropecuaria Brasileira, 2014)
An analytical procedure for determining the most efficient alternative in a broiler operation is presented. Maximum economic yield was the criteria of efficiency. The relations between input and output were obtained from an experiment in which the ration fed was considered as an independent variable. Feed and broiler prices were those of the Fortaleza market in September and October of 1966. A function of production was used to determine the optimum killing time. Under tine conditions of this study this occurred when the broiler had consumed 6.13 kg of feed. There was definite evidence that under certain circumstances it may be advantageous to ignore the optimum yield for a given lot of broilers in order to obtain the maximum number of lots from the facilities available.